Atorvastatin Ameliorates Neuroinflammatory Response in Experimental Intracerebral Hemorrhage Rats through the GSK-3β/β-Catenin Pathway - Zhao, Jing; Li, Mei; Zhang, Lingling; Zhang, Qi (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: This study aimed to elucidate influence of Atorvastatin (ATV) on the neuroinflammatory response in experimental Intracerebral Hemorrhage (ICH) through the GSK-3β/β-catenin Signaling Pathway (SPW). Materials and Methods: Forty-five rats were randomly rolled into Sham, ICH (established using the Fredrik methodology) and ATV intervention (ICH model+10 mg/kg ATV) groups, each comprising 15 rats. Neurological deficits in rats were assessed using the Garcia methodology. Brain Water Content (BWC) was measured via wet-dry methodology. Nissl staining was conducted to observe Brain Tissue (BT) histological changes and count undamaged neurons. Expression Levels (ELs) of β-catenin, GSK-3β and p-GSK-3β in BT were detected. Levels of Inflammatory Factors (IFs) Tumor Necrosis Factor (TNF)-α, Interleukin (IL)-1β and IL-6 in rat cerebrospinal fluid were measured. Results: Relative to Sham group, ICH group exhibited decreased postoperative neurological behavior scores, β-catenin gene mRNA ELs and β-catenin protein levels, along with a reduction in the number of intact neurons (p<0.05). BT BWC, GSK-3β gene levels, p-GSK-3β and GSK-3β protein ELs were greatly increased, that is, p<0.05, while IL-6, IL-1β and TNF-α in cerebrospinal fluid were markedly elevated (p<0.05). In comparison to ICH group, ATV group showed increased neurological behavior scores, β-catenin gene mRNA levels and β-catenin protein levels, with an increase in the number of intact neurons (p<0.05). Moreover, BWC, GSK-3β gene mRNA ELs, p-GSK-3β and GSK-3β protein ELs, as well as IFs, were notably decreased (p<0.05). Conclusion: ATV, through regulation of the GSK-3β/β-catenin SPW, inhibits inflammatory reactions and cellular damage, thereby ameliorating neurological dysfunction and neuroinflammatory responses in experimental ICH rats.
Keywords: Atorvastatin; Experimental cerebral hemorrhage; Gsk-3β/β-catenin signaling; pathway; Inflammatory reaction; Neuroprotection